Conforto térmico do transeunte : a porosidade urbana como condicionante da ventilação - Silva, Fabiana Trindade da (2014)
The changes of urban structures associated with the non-inclusion of climate issues in Zoning Ordinances generate environmental consequences that may contribute to the passerby’s thermal discomfort. For regions of hot and humid weather, as the case of Vit